PERAN LEMBAGA KEUANGAN SYARIAH DALAM MENGHADAPI PANDEMI COVID-19 - Nahda, Lutfia; Alwasi, Kila; Febrianti, F; Arsita, Dharma Jayanti; Aprilia, Livia Risma (Jurnal Ekonomi & Bisnis, 2024)
The Covid-19 pandemic has had a major impact on the economy, and the finance and banking sector is no exception. Seeing the economic impact of the Covid-19 pandemic, the government needs to take effective steps to keep the Indonesian economy stable. This is an opportunity as well as a challenge for sharia economic actors to be able to increase their role in helping the government stabilize the Indonesian economy. Given that sharia financial institutions are able to survive the crisis and are able to show good performance during the Covid-19 pandemic so that they remain stable and provide benefits, comfort, and security for their customers. Therefore, this study aims to identify the effective role of sharia financial institutions in dealing with various Covid-19 pandemics. This article uses qualitative data analysis with descriptive-critical methods and through a literature study approach. The results of this study indicate that Islamic financial institutions have shown a significant role in dealing with the Covid-19 pandemic by adopting various innovative strategies in accordance with Islamic principles. Islamic financial institutions have not only succeeded in maintaining financial stability, but have also contributed to economic recovery efforts by supporting the most affected sectors. By continuously increasing innovation and collaboration will strengthen the Islamic financial system in the future Islamic financial institutions can play a bigger role in the global economy.